Evaluation of the Results of Attitudes and Self-Efficacy of Middle School Students in Science Subjects - Retni S, Budiarti; Dwi Agus, Kurniawan; Elza, Triani; Rahmat, Perdana (Journal of Education Reseach and Evaluation, 2021)
Good attitudes and self-efficacy in each student's personality are very important to have in order to maximize the activities and learning outcomes of each student. The urgency of this research as a reference to the educators in conducting teaching to find out the significant and continuous impact on the success of student achievement in science subjects and student performance on the variables of self-efficacy and attitude in learning. This study aims to determine the differences and the relationship between attitudes and self-efficacy of students in science subjects. The type of research is comparative quantitative. The number of respondents as a sample is 74 students. The data collection technique used simple random sampling. The results of the study using the T test, which is a significant difference in student attitudes in science lessons, both female and male students in class VII A and class VII B. From the results of the T test for self-efficacy, there are differences in student self-efficacy in lessons Science both students and male students in class VII A and class VII B. The results of the correlation test between students' attitudes and self-efficacy towards science subjects in class VII A and VII B showed that attitudes and self-efficacy were related. This study has limitations including researchers only measuring the attitudes and self-efficacy of students in class VII. Recommendations for further researchers can research or measure students' interests and motivations or make generalizations about this research.